Implementation mechanism of ethics in business organizations - Jalil, Md Abdul; Azam, Ferdous; Rahman, Muhammad Khalilur (Canadian Center of Science and Education, 2010)
Ethics and ethical behavior are issues which are increasingly being focused on the business community today. People are becoming more concerned about what is actually happening in business organizations in the name of competition, growth, and profitability. Organizations are crossing the red zone of ethics and ethical behaviors. A growing number of organizations are constantly surveying and evaluating the unethical practice in business organizations worldwide. The purpose of this paper is to examine the importance of ethical practices and how to implement those ethical practices in business organizations. It is empirically proved that ethical practices in business organizations help to create favorable relationships with other organizations and can also establish long-term positive relationships with existing and potential future customers. Descriptive and analytical research methodology is applied in this research paper. The findings of this paper is that it is very essential to have a code of business ethics in every business organization and this code of business ethics must be implemented in the organization in objective and effective way.